The influential factors affecting occupational stress : A study among secondary school teachers in Kelantan / Nurul Bariyah Ibrahim ... [et al.] - Ibrahim, Nurul Bariyah; Hamzah, Nor Hazreeni; Ibrahim, Nur Safwati; Mohd Fauzi, Noor Zafarina (2021)
Occupational stress or workload stress is the physical or psychological factor that has been pushed by any force behind its range of stability, producing a strain within the individuals. Occupational stress experienced by teachers is attributed by their workload. It can cause anxiety and depression which can lower the teacher's ability to function at work or in their daily life. The purpose of this study is to identify the relationship of time management, work-related stressors, self-motivation and teaching experience on the occupational stress among teachers of secondary school in Kota Bharu. A set of questionnaire was distributed to 200 teachers from daily and cluster secondary schools in Kota Bharu. Using the Multiple Linear Regression method derived with statistical tool Statistical Package for the Social Sciences (SPSS) version 22, the finding shows that there is a significant linear relationship between time management, work-related stressors, teaching experience, self-motivation and the occupational stress. The regression analysis shows that the factors of time management, work-related stressors, teaching experience and self-motivation affect occupational stress. Furthermore, this study also found that time management is the most important factor that affects the level of occupational stress among the teachers. It proved that the effectiveness of individual time management is very important in order to manage stress level. Therefore, it suggests that school teachers need to be provided with time management training course and educators motivation program